Alimentación del bonito Sarda chiliensis (Pisces: Scombridae) en el norte de Chile (Revista de Biología Marina y Oceanografía, 2023)
The diet of Sarda chiliensis from artisanal fishing in northern Chile from May 2017 to March 2018 was analyzed. Stomach content analysis resulted that the most frequent and abundant prey was Pleuroncodes monodon with the highest value of Index of Relative Importance in the diet (%IRI= 45.8) followed by Engraulis ringens. No correlation was found between the length of the main prey (P. monodon and E. ringens) and the size of the predator. S. chiliensis tended to be a generalist predator (Bi= 0.75) with a trophic position NT= 4.3, a trophic level characteristic of species considered top predators.